Identifying barriers and drivers to vaccination: A qualitative interview study with health workers in the Federation of Bosnia and Herzegovina. Issue 8 (18th February 2020) - Musa, Sanjin; Skrijelj, Venesa; Kulo, Aida; Habersaat, Katrine Bach; Smjecanin, Mirsad; Primorac, Emilija; Becirovic, Darija; Jackson, Cath
Abstract: Background: Vaccination coverage in Bosnia and Herzegovina has been declining over recent years. A World Health Organization Tailoring Immunization Programmes (TIP) project is underway to gain insights into the underlying reasons for this, to develop tailored interventions. As part of TIP, this study aimed to investigate the views of health workers on their barriers and drivers to positive childhood vaccination practices. Methods: Face-to-face qualitative interviews explored 38 health workers' views on vaccination coverage, their vaccination attitudes, and system, programme and institutional influences on their vaccination practices. The data were analysed using content analysis and organised by the COM (Capability, Opportunity and Motivation) factors. Findings: Very few differences in barriers and drivers were evident between high and low coverage primary care centres or across different professional roles. Capability: Drivers included awareness of the risks of low vaccination coverage, regular use of the Rulebook and Order, knowledge of how to advise parents on mild side effects and recognition of the importance of good communication with parents. Key barriers were the use of false contraindications to postpone vacination and poor skills in tailoring communication with parents. Opportunity: Drivers were sufficient time for adminstering vaccination and good availability of vaccines. Several barriers were evident: lack of implementation of mandatory vaccination, no uniform recall and reminder system or system for detecting under-vaccinated children, staff shortages and lack of time to discuss vaccination with parents. Motivation: Drivers were a belief in the value, safety and effectiveness of vaccination and seeing that they have an important role to play. Barriers were a tendency to blame external factors e.g. anti-vax movement and a fear of being blamed for adverse events. Conclusions: The study identified complex and inter-related barriers and drivers to health worker positive vaccination practices. These insights will now inform a process to identify and prioritize interventions.